A case of generalised pruritus of unknown origin, associated with a paraproteinaemia, treated with citalopram - Khin Y Kyaw; Zhenghao Wang; Sophia Neda; George W M Millington (Clinical and Experimental Dermatology, 2026)
We report a case of generalised pruritus in a 67 year old woman, associated with a paraprotein, responding to treatment with a selective serotonin reuptake inhibitor (SSRI) in the absence of any psychological disorder, after failing topical treatments, antihistamines and mirtazapine.